Severe Wolcott-Rallison syndrome due to a nonsense mutation in the first exon EIF2AK3 - Diliara N. Gubaeva; Dmitry N. Laptev; Anatoly N. Tiulpakov; Lidia M. Petrova (Сахарный диабет)
Wolcott-Rallison syndrome is a rare autosomal recessive disease characterized by neonatal diabetes mellitus in combination with osteodysplasia and liver failure. This disease is the most common cause of neonatal diabetes mellitus in consanguineous families. Wolcott-Rallison syndrome is associated with mutations in the EIF2AK3, the gene encoding a transmembrane enzyme PERK (pancreatic endoplasmic reticulum kinase) which inhibits the synthesis of proteins in the event of misfolding in the endoplasmic reticulum. In addition to the core symptoms patients may develop multisystemic clinical manifestation including acute renal and liver failure, short stature, exocrine pancreatic insufficiency, neuro-motor deficit, hypothyroidism, anemia, neutropenia, recurrent hypoglycemia. The disease is characterized by high mortality, more than 50% of patients die from fulminant liver failure. The awareness of Wolcott-Rallison syndrome is extremely low due to the rarity of detection, however in view of the severity of the disease and the unfavorable prognosis patients with this syndrome require timely diagnosis and care of well-organized team of specialists.